PEMBUATAN BIOETANOL DARI TEPUNG AMPAS TEBU MELALUI PROSES HIDROLISIS TERMAL DAN FERMENTASI SERTA RECYCLE VINASSE (PENGARUH KONSENTRASI TEPUNG AMPAS TEBU, SUHU DAN WAKTU HIDROLISIS) (Jurnal Teknik Kimia USU, 2015)
The purpose of this research are to study the effect of sugarcane bagasse powder concentration, hydrolysis temperature and time on the yield of glucose and the level of glucose by recycle vinasse process. Raw sugarcane bagasse as primary material was obtained from sugarcane juice shop. Observed variabels were concentration of sugarcane bagasse, hydrolysis time and temperature. Sugarcane bagasse is powdered by blender and then mixed with aquadest (2,94; 3,85; 4,76%) and hydrolized in the hydrolysis tank. The hydrolysis process occured at 1, 1,5 and 2 hours and temperature 135, 150 and 165°C. The hydrolysis products were tested for its glucose, lignin and cellulose composition. After that, the product was fermented in order to produce bioethanol. The fermented product was filtered for its vinasse and it will be used as the feed of hydrolysis recycle process. Result showed that yield of glucose increases as the increase of sugarcane bagasse powder concentration, hydrolysis time and temperature. But, yield of glucose increases from 1 until 1,5 hour of hydrolysis time and then decreases from 1,5 to 2 hour of hydrolysis time. The highest yield of glucose (31,022%) was obtained at concentration 2,94%, 165 °C and 2 hours of hydrolysis time. Lignin and cellulose level fluctuated as the increasing of hydrolysis temperature. This might be caused by the non-uniform composition by the raw materials.